KERAGAMAN GENETIK DAN HERITABILITAS KARAKTER UBI BENGKUANG (Pachyrhizus erosus (L.) Urban) - Budi Martono (Biofarm Jurnal Ilmiah Pertanian, 2010)
Genetic Variability and Heritability of Tuber Characters of Yam Bean (Pachyrhizus erosus (L.) Urban) The research objectives to know genetic variabilities and heritabilities of character tubers of yam bean. Fiveteen accessions germplasm of yam bean were evaluated in Cikeumeuh Experimental Garden, Indonesian Center Agricultural Biotechnology and Genetic Resources Research and Development (ICABIOGRAD), Bogor from August 2003 until March 2004, using a randomized complete block design with three replications. Result of the experiments indicated that diameter and weight of tubers had a wide range genetic variability. Meanwhile the tubers length and diameter of base tubers were narrow genetic variabilities. The characters of tubers diameter, diameter of base tubers, and tubers weight showed moderate heritability values;  heritability in tubers length were low. Key words: genetic variability, heritability, tuber characters, Pachyrhizuserosus (L.) Urban